STUDENTS’ ENTHUSIASM IN LEARNING IN THE COVID-19 OUTBREAK - Ali Akbarjono; Elvani Belawati; Zelvia Liska Afriani (Journal of Research on Language Education, 2022)
The purpose of this study is to determine student excitement for studying English during the Covid-19 outbreak, as well as the ways in which teachers encourage student enthusiasm for learning English throughout the outbreak. A qualitative research design was adopted in this study. The subjects of this study are students of class XI in MAN 1 Model Bengkulu class XI A, totaling 30 students. The study's findings revealed that pupils in class XI MAN 1 Model Bengkulu are enthusiastic about learning English. Based on observations and interviews with students from MAN 1 Model Bengkulu class XI. As indicated by the reduction in the English value of class XI MAN 1 Model Bengkulu pupils during the Covid-19 outbreak, the findings show that most students have a low level of excitement when studying. The observation checklist and interview used to observe the activities of students and teachers in the English class. To analyzing the data, the researcher was apply (1) data reduction; (2) data display; and (3) drawing and verifying conclusionTeachers use various strategies so that the enthusiasm of students in learning English during the Covid-19 outbreak continues to increase, namely by using interesting learning videos and giving quizzes to students. Keywords: Student Enthusiasm, Learning English, Covid-19 Outbreak.